The twelve dancing princesses - Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859.; Le Cain, Errol ([New York] : Puffin, 1978)
A retelling of the tale of twelve princesses who dance secretly all night long and the poor soldier who follows them and discovers where they dance.
Translation of: Die zertanzten Schuhe.
4.3
K-3
Keywords: Fairy tales; Folklore -- Germany; Fairy tales; Folklore -- Germany